AN ANALYSIS OF COMMUNICATION STRATEGIES USED BY SURF GUIDES IN THEIR INTERACTION TO FOREIGNERS - Yudistian, Randi; Suarnajaya, I Wayan; Dewi, Kadek Sintya (International Journal of Language and Literature, 2019)
Tourism is a field which demands people to have good communication skills including the people who work as surf guides in Medewi Beach tourism object. In some occasions, they faced problems in conducting communication and solved them by using communication strategy. This study aimed at finding out and describing types of communication strategy which were used by the surf guides in their interaction to foreigners in Medewi Beach. This study was in the form of descriptive qualitative and the data were analyzed by using Dornyei’s communication strategy theory. The data were obtained through observation and interview method by involving five surf guides. There were 177 communication strategies found and classified into twelve types, namely Approximation, Word Coinage, Circumlocution, Literal Translation, Code Switching, Appeal for Help, Nonlinguistic Signal, Topic Avoidance, Message Abandonment, Use All-purpose Word, Foreignizing, and Stalling or Time-gaining. The result of data analysis showed that Approximation became the strategy which was most frequently used by the surf guides for 52 occurrences. Based on the interview results, the guides’ reason for doing the Approximation was because they learned English mostly by self-taught or practiced English autodidactically with foreigners. Thus, they did not pay attention to grammar which triggered the Approximation happening.